Working on Buildings’ Energy Performance Upgrade in Mediterranean Climate - Dimitris Al. Katsaprakakis; Georgios Zidianakis; Yiannis Yiannakoudakis; Evaggelos Manioudakis; Irini Dakanali; Spyros Kanouras (Energies, 2020)
This article aims to present the results from studies on the energy performance upgrade of buildings and facilities located in Crete, Greece, in a typical Mediterranean climate. In Mediterranean islands, the most buildings remain uninsulated, classified in C or even lower energy performance rank. In this article four reference buildings and one sports facility are investigated: a residential building, a municipality building, a school building, a museum and the Pancretan Stadium. Detailed calculations based on the computational simulation of each examined facility were executed, giving accurate results on the heating and cooling loads, both for the existing conditions and after the integration of the proposed passive measures. Thorough dimensioning and energy calculations have been executed for specific active energy systems too, particularly proposed for each examined case. With this parametric approach, the article indicates the effect and the economic efficiency of the proposed active or passive measures for each examined facility, expressed with specific key performance indicators. The common conclusion for all investigated cases is the huge margin for energy saving, which can reach 65% with regard to the existing annual consumptions. The payback period of the introduced energy upgrade measures can be as low as 15 years.